2013
DOI: 10.1371/journal.pone.0057913
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-to-Fine Construction for High-Resolution Representation in Visual Working Memory

Abstract: BackgroundThis study explored whether the high-resolution representations created by visual working memory (VWM) are constructed in a coarse-to-fine or all-or-none manner. The coarse-to-fine hypothesis suggests that coarse information precedes detailed information in entering VWM and that its resolution increases along with the processing time of the memory array, whereas the all-or-none hypothesis claims that either both enter into VWM simultaneously, or neither does.Methodology/Principal FindingsWe tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 59 publications
4
37
0
Order By: Relevance
“…The authors concluded that for complex objects, the CDA might reflect information load in VSTM that is determined by both number and resolution of the objects. It has further been shown that the resolution of VSTM representations increases with the duration of the memory array (Gao et al, 2013). For short processing times, like that used in the current study and in most similar studies, the CDA reflects maintenance of coarse representations.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that for complex objects, the CDA might reflect information load in VSTM that is determined by both number and resolution of the objects. It has further been shown that the resolution of VSTM representations increases with the duration of the memory array (Gao et al, 2013). For short processing times, like that used in the current study and in most similar studies, the CDA reflects maintenance of coarse representations.…”
Section: Discussionmentioning
confidence: 99%
“…This prediction seems to have been supported by a recent ERP study. Gao, Ding, Yang, Liang, and Shui (2013) used the CDA component as a neural marker and asked participants to remember two and four complex shapes in different exposure duration conditions (100 ms vs. 500 ms). They observed that CDA was higher for four complex shapes than two complex shapes at 100 ms exposure duration, yet this difference vanishes at 500 ms exposure duration.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported that manipulating the stimulus contrast in the change detection paradigm, while resulting in an impaired behavioral performance, did not have any effect on the CDA (Gao et al, 2013; Ikkai et al, 2010; Luria et al, 2010; Ye et al, 2014). This result is significant because it reveals a dissociation between the low accuracy performance (usually taken as a marker of VWM capacity) and the intact CDA amplitude, and serves as additional evidence that the CDA does not simply reflect the task difficulty.…”
Section: The Cda As An Index Of Vwm Capacitymentioning
confidence: 99%